Analisis Semantik: Gramatikal dan Leksikal Metamorfosa Antologi Puisi Karya Wita Nfa - Martha Amanda Sari; Rani Jayanti (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Poetry is known as a form of written art that is rich in meaning and symbolism. One collection of poems that is interesting to study in terms of meaning is the collection of poems by Wita Nfa entitled “Metamorphosis.” This analysis uses three poems, namely Bertandang, Fall, and Rona. The method used in this study is descriptive qualitative with several in-depth explorations, notes, and grouping of meaning elements. This study focuses on the type of meaning of each word, whether it is lexical or grammatical, and will also analyze the meaning of each word. The results of this study produced 65 words, including lexical and 46 grammatical words. This study also reveals the implied meanings that the author attempts to convey because Wita Nfa's poetry has a unique and implied style of language. Therefore, this study was conducted to gain a deeper understanding of the messages that the poet wants to convey and to explain how language and symbols in poetry can influence the feelings and thoughts of readers. We hope that the results of this study will help readers better understand the meaning in poetic literary works.